Connections Matter: Family Centers and German Social Policy - Onno Husen; Philipp Sandermann (Social Work & Society, 2018)
German social policy has promoted family centers for the past decade, and in that period they have spread considerably. At first glance, this development suggests that contemporary social policy in Germany is implementing new services to support families directly. We question that. To support our critical perspective, we present some of the key results of a content analysis of political documents promoting family centers in the most populous German state of North Rhine-Westphalia. Our analysis shows that the spread of family centers in North Rhine-Westphalia is founded on particular assumptions about families, assumptions that create connections with various traditional fields of federal social policy in Germany. Drawing on Luhmann's theory of social systems and on new institutionalism, we conclude that the case of family centers in North Rhine-Westphalia shows how the "new" idea of family centers does not contradict but conform to pre-existing, long-established institutional structures social services in Germany. In the broader historical context of German social policy, therefore, the case of North Rhine-Westphalia illustrates how family centers should not be interpreted as family services per se.